Analysis of the impact of export specialisation and investment attractiveness on the processes of innovation diffusion in the processing industry in Poland - Salamaga, Marcin (Publishing House of Wroclaw University of Economics and Business, 2024)
The fundamental ways of building innovativeness of the economy are the creation and diffusion of innovation, the latter of which is the dispersal of new technological, organizational, marketing solutions as well as knowledge among imitator enterprises, and copycats (the ‘spillover effect’). Important determinants of innovation diffusion include the inflow of foreign capital (in the form of FDI) and foreign trade. Few empirical studies exist that attempt to explain the sources of innovation diffusion in the Polish economy applying quantitative tools used in contemporary statistics and econometrics. The existing research gap makes it difficult to reliably assess the actual cause-and-effect relationships between spillover processes and macroeconomic variables. This article sought to determine the nature and strength of the impact of investment specialisation (and investment attractiveness) as well as industry export specialisation on the phenomenon of penetration of innovation in the Polish processing industry. The occurrence of innovation diffusion and its dynamics were investigated using the logistic function econometric model. To study the impact of the specialisation, according to FDI located in Poland, and specialization of export on the process of innovation diffusion, dynamic models of error correction estimated for selected industrial processing industries were used. The obtained results allowed to answer the questions: in which industries has innovation diffusion occurred, in which was it the fastest, and to what extent was it the effect of investment attractiveness, and to what degree of the export specialization of the industry?
Argumenta Oeconomica, 2024, Nr 2 (53), s. 130-143
Keywords: ECM; RCA; FDI; innovation diffusion; Poland